Whether physical activity is important in patients with heart disease? - Szmit, Sebastian; Filipiak, Krzysztof J. (Przewodnik Lekarza/Guide for GPs, 2007)
The most frequent causes of organic heart disease are complications of arterial hypertension and of coronary artery disease. Exercise tolerance is an expression of advanced heart disease and quality of life. Exercise test has high prognostic value in the population of patients with cardiovascular diseases. Physical activity favourably influences classical risk factors of cardiovascular diseases such as arterial hypertension, hyperlipidaemia and obesity. Regularly repeated exercise not only reduces symptoms of heart disease, but actually reduces mortality. At the basis of the positive influence of physical activity lies the molecular anti-inflammatory, anti-thrombotic and anti-arrhythmic activity.